The Relationship between Psychological ‎Stress and Perceived Self-efficacy in Mothers ‎of Children with Autism Spectrum Disorder in ‎Jordan - Muhaidat ‎, Mohammad; Abu Sarah, Mariam (Jordan Journal of Educational Sciences, 2021)
This study aimed to verify the relationship between psychological stress and perceived self-efficacy among mothers of children with autism spectrum disorder in the governorate of Irbid. The study population consisted of (170) mothers, while the study sample consisted of (101) mothers chosen in a simple random method. To achieve the goals of the study, measures of psychological stress and perceived self-efficacy were applied. The psychological stress scale consisted of (36) items divided into three dimensions: the distress (sadness) of the parents, the interaction between the parents and the child and the child problems. The perceived self-efficacy measure consists of (17) items. The results showed that the level of psychological stress among mothers came with a high degree and that the level of perceived self-efficacy was average. The results also showed a statistically significant inverse relationship at the level of significance (α = 0.05) between the level of psychological stress and perceived self-efficacy among mothers of children with autism spectrum disorder